Mapping application-level components into hierarchical systems resources - Alves, Albano (2009)
The appropriate organization of application components and their right mapping into physical resources is fundamental to fully exploit cutting edge technologies especially when hierarchical architectures are used. We present a new approach to combine application modelling with resource management. The proposed programming model allows the mixing of message-passing and global memory facilities and integrates them with the high-level abstractions provided for specifying and organizing application components and resources. The methodologies and tools we had designed pave the way to build complex systems through the use of cooperative applications, executed simultaneously, involving multiple users, thus extending the MPMD model.